PENGEMBANGAN STRATEGI PEMBELAJARAN BERBASIS AYAT-AYAT KAUNIYAH DALAM PEMBENTUKAN KARAKTER SISWA SMA/MA DI PROPINSI LAMPUNG - Umi Hijriyah; Edi, Relit Nur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The purpose of this research is to know the feasibility and response of learning strategies Tafakur Ayat Kauniyah students grade X SMA/MA Strategy oriented tafakur verse kauniyah which means biology learning needs to rest on tafakur activities, namely brooding, thinking, and considering something seriously about the universe. This research so that students have an understanding with the kauniyah verse has the meaning of the embodiment of the majesty of Allah SWT in the form of a universe with study materials in Biology that hold wisdom for those who study it. Using borg and gall development methods. After being tested obtaining a category very worthy of use in SMA /Madrasah Aliyah modified with Kauniyah Verses and can make students more motivated to understand and apply in daily life change the habits and character of students to be better and response educators with very category.